'Feel the Feeling': Psychological practitioners' experience of acceptance and commitment therapy well-being training in the workplace. (August 2016) - Wardley, Matt NJ; Flaxman, Paul E; Willig, Carla; Gillanders, David
This empirical study investigates psychological practitioners' experience of worksite training in acceptance and commitment therapy using an interpretative phenomenological analysis methodology. Semi-structured interviews were conducted with eight participants, and three themes emerged from the interpretative phenomenological analysis data analysis: influence of previous experiences, self and others and impact and application . The significance of the experiential nature of the acceptance and commitment therapy training is explored as well as the dual aspects of developing participants' self-care while also considering their own clinical practice. Consistencies and inconsistencies across acceptance and commitment therapy processes are considered as well as clinical implications, study limitations and future research suggestions.